Предмет: Алгебра, автор: KristinaAndreevna

Разложите на множители
аb- b^{2}
3x+6xy+ 9x^{2}
6xy+x
 x^{3}-2 x^{4}+3 x^{5}
c^{2}-c
2(x-y)-a(x-y)
7(x+y)-a(x+y)
2(a-b)+c(b-a)
2a(b-3)-5c(3-b)
 x^{4}+ x^{3}- x^{2}
a( x^{2}+ y^{2})+b( x^{2} + y^{2} )
ax+bx+ay+by
 12n^{3}+ n^{2}  -n-12

Ответы

Автор ответа: inblu
0
b(a-b) \ 3x(1+2y+3x) \ x(6y+1) \ x^3(1-2x+3x^2) \ c(c-1) \ (x-y)(2-a) \ (x+y)(7-a) \ 2(a-b)+c(b-a)=2(a-b)-c(a-b)=(a-b)(2-c) \ 2a(b-3)-5c(3-b)=2a(b-3)+5c(b-3)=(b-3)(2a+5) \ x^2(x^2+x-1) \ (x^2+y^2)(a+b) \ (ax+bx)+(ay+by)=x(a+b)+y(a+b)=(a+b)(x+y) \ (12n^3-12)+(n^2-n)=12(n^3-1)+n(n-1)= \ 12(n-1)(n^2+n+1)+n(n-1)=(n-1)(12(n^2+n+1)+n)= \ =(n-1)(12n^2+12n+1+n)=(n-1)(12n^2+13n+1)= \ =(n-1)*12(x+ frac{1}{2})(x+ frac{7}{12})
Похожие вопросы
Предмет: Математика, автор: muslimaodilova155